1993
DOI: 10.1002/app.1993.070490908
|View full text |Cite
|
Sign up to set email alerts
|

Polymerization of olefins through heterogeneous catalysis XI: Gas phase sequential polymerization kinetics

Abstract: SYNOPSISA unique series of ethylene and propylene sequential polymerization experiments have been carried out in a stirred bed gas phase reactor using unsupported Stauffer AA catalyst ( TiC13 * f AlC13). Several interesting kinetic results were observed. It was found that propylene causes rate enhancement for a subsequent ethylene polymerization but that ethylene causes a rate reduction for a subsequent propylene polymerization. Furthermore, the rate enhancement /reduction effect increases with the duration of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

1997
1997
2007
2007

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…Also shown in Figure 10 is the base case EF base , propylene consumption rate upon addition of ethylene. However, Chen et al 11 reported that which is calculated from the copolymerization reaction equation under the assumption that the ethylene polymerization reduces the subsequent 8G42 96125T / 8G42$$125T 07-29-97 17:51:29 polca W: Poly Chem polymerization reaction rate in an ethylene-propylene sequential polymerization reaction. Two major viewpoints exist as far as the rate enhancement effect is concerned; monomer diffusion theory and kinetic effect theory.…”
Section: Rate Enhancement Effectmentioning
confidence: 98%
“…Also shown in Figure 10 is the base case EF base , propylene consumption rate upon addition of ethylene. However, Chen et al 11 reported that which is calculated from the copolymerization reaction equation under the assumption that the ethylene polymerization reduces the subsequent 8G42 96125T / 8G42$$125T 07-29-97 17:51:29 polca W: Poly Chem polymerization reaction rate in an ethylene-propylene sequential polymerization reaction. Two major viewpoints exist as far as the rate enhancement effect is concerned; monomer diffusion theory and kinetic effect theory.…”
Section: Rate Enhancement Effectmentioning
confidence: 98%
“…Despite the successful application of gas-phase ethylene polymerization processes, which have been used commercially for more than 30 years, only a few papers in the open literature have been published on gas-phase ethylene polymerization in bench-scale reactors. Experiments in bench-scale reactors are essential for investigating the effects of operating conditions on product properties, collecting information for mathematical models, and designing commercial reactors. Unfortunately, experimental investigations in the laboratory are impeded by problems related to addition and mixing of high-activity catalysts, maintaining low impurity levels, and controlling reactor temperature, which can lead to poor reproducibility of polymerization rate and polymer properties.…”
Section: Introductionmentioning
confidence: 99%
“…The intrinsic complexity of olefin copolymerization with Ziegler–Natta catalysts demands reaction models to control and better understand the polymerization process. The Ziegler–Natta process is one of the most studied polymerization systems for modeling,1–17 and several reviews on olefin polymerization with Ziegler–Natta catalysts are available in the literature 18–26…”
Section: Introductionmentioning
confidence: 99%